Akuntansi Syariah di Indonesia: Integrasi Nilai Syariah dan Pancasila pada Harmonisasi Global - Absari, Dyatri Utami Arina (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This article examines Islamic accounting in Indonesia as a normative–hybrid system shaped by the integration of maqāṣid al-sharīʿah, Pancasila ideology, and the pressures of global accounting harmonization. Employing an integrative literature review, the study synthesizes conceptual, empirical, and normative–legal scholarship to analyze the interaction between Islamic values, national ideology, and international standards, particularly the International Financial Reporting Standards (IFRS). The findings indicate that Islamic accounting in Indonesia cannot be adequately explained through purely technocratic or religio-centric perspectives. Instead, it functions as a contextual normative system in which Islamic ethics and Pancasila serve as core guiding logics, while global standards, governance mechanisms, sustainability reporting, and digitalization operate as adaptive instruments. The study identifies persistent challenges, including partial IFRS harmonization, fragmented regulatory governance, and the risk of formalistic compliance that weakens ethical and social objectives. This article contributes by proposing the Indonesian Contextual Normative–Hybrid Islamic Accounting model, offering a framework for developing an ethical, socially grounded, and globally adaptive Islamic accounting system